How to deal with the disadvantages of living in dense societies: traffic rules in leaf-cutting ants - Farji-Brener, Alejandro G. (Revista Colombiana de Entomología, 2021)
Transporting food from production centers to consumption centers is a challenge for densely populated societies. To avoid delays, the trail system must be efficient and the behavior of the transporters must reduce the probability of collisions. This work, describes how Leaf-Cutting Ants (LCA) solve these dilemmas by optimizing their trail design and performing behaviors that avoid bottlenecks and delays. On the one hand, the LCA build trails wide enough to avoid traffic jams at times of peak foraging activity. Also, at the bifurcation points, the sum of the branching trail widths is always higher than the width of the precedent trunk trail. Finally, LCA builds their branching trails with angles that reduce the maintenance cost of the new trail sector or of the total trail length, depending on which factor is more limiting. On the other hand, LCA shows a range of behaviors that avoid delays: minima workers can travel on the leaf fragments thereby reducing flux density, unloaded workers remove obstacles from the trail, ants carry extra-large loads mainly during situations of low traffic, ants maintain their lane when turning, and foragers show priority rules during jam situations. These examples illustrate how ants, using simple behavioral rules that arise from positive interactions among individuals, can solve complex problems such as traffic regulation.